Fundamental period and damping of experimentally tested reinforced-concrete building under different damage levels - Brandis, Adriana (Array, 2019)
Blind prediction of the dynamic behavior of experimentally tested structures employing numerical models is a professional and academic challenge that brings to test existing knowledge and produces a new understanding of the performance of structures. The pre-test model is usually first validated through the fundamental period. This only adds certainty to the elastic model. However, the post-elastic behavior is steered by damping inter alia. This property of the model is usually assessed based on empirically derived analytical expressions. This paper investigates to what extend analytical expressions for estimation of the fundamental period and damping give a good prediction of numerically and experimentally obtained counterparts. As a governing vehicle of this paper, experimentally obtained data from the 2012 blind test contest was used. The experiment included testing of a reinforced concrete frame using a shaking table and motions of increasing intensity levels, wherein the frame was not repaired between the tests. Besides the literature overview of analytical expressions for estimation of fundamental period and damping, this paper presents dynamic properties of experimentally tested building obtained from pseudo-free vibrations. The results of this study convey that analytical expressions underestimate experimentally and numerically obtained fundamental period, but give a good prediction of damping.